2017
DOI: 10.1016/j.jjcc.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of causative organism in cardiac implantable electronic device infections

Abstract: The causative organism is mostly S. aureus and CoNS. Detection of S. aureus or Gram-negative bacteria means that it is more likely a causative organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 19 publications
6
19
0
Order By: Relevance
“…Over recent years, the growing use of CIEDs has led to an increase in the incidence of IE due to difficult-to-treat organisms, such as methicillin- resistant Staphylococcus aureus, Candida spp., and GNB (19)(20)(21)(22). It has been documented that a significant percentage of device-related IE cases (from 16% to 23%) are caused by non-Staphylococcus species (23,24), represented mostly by GNB, with a predominance of Pseudomonas aeruginosa (24). It has also been demonstrated that, in contrast to the pattern for infections with Gram-positive bacteria, among patients with CIED-related IE, the GNB isolated from the pocket or infected skin tissue is highly concordant with the strain isolated from the bloodstream (23).…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, the growing use of CIEDs has led to an increase in the incidence of IE due to difficult-to-treat organisms, such as methicillin- resistant Staphylococcus aureus, Candida spp., and GNB (19)(20)(21)(22). It has been documented that a significant percentage of device-related IE cases (from 16% to 23%) are caused by non-Staphylococcus species (23,24), represented mostly by GNB, with a predominance of Pseudomonas aeruginosa (24). It has also been demonstrated that, in contrast to the pattern for infections with Gram-positive bacteria, among patients with CIED-related IE, the GNB isolated from the pocket or infected skin tissue is highly concordant with the strain isolated from the bloodstream (23).…”
Section: Discussionmentioning
confidence: 99%
“…CIED infections are an unfortunate but not unexpected risk, estimated to be approximately 0.5% to 1% for first-time implantation and 1%–5% for replacement or upgrade 7. The most common causative organisms of CIED infection are consistently identified as Staphylococcus aureus and coagulase-negative staphylococci 7 16. A 2017 Cleveland Clinic Journal of Medicine report indicated that mycobacterial infections represented just 0.2% of their pacemaker infections in contrast to 68.4% caused by Staphylococcus and 8.9% caused by gram-negative organisms 7.…”
Section: Discussionmentioning
confidence: 99%
“…Infective endocarditis is a serious infectious disease with high associated morbidity and mortality. Identification of the causative agents is, therefore, crucial for improving the clinical outcome [1]. Clinically, infective endocarditis is generally diagnosed based on positive blood cultures, removed leads, and/or infected pocket material [1].…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the causative agents is, therefore, crucial for improving the clinical outcome [1]. Clinically, infective endocarditis is generally diagnosed based on positive blood cultures, removed leads, and/or infected pocket material [1]. Species belonging to the genera Streptococcus, Staphylococcus, and Enterococcus are the primary causative organisms of infective endocarditis [2].…”
Section: Introductionmentioning
confidence: 99%